Bat guano fertilizer as a source of Betacoronavirus: First molecular evidence linking Rhinolophus coelophyllus to viral reservoirs in Thailand - Rattikan Suwannasing; Thachawech Kimprasit (PLoS ONE, 2026)
Commercial bat guano fertilizers distributed in Thailand were screened for the presence of coronavirus genomes to assess potential public health risks. A total of 41 samples were analyzed for Alphacoronavirus (AlphaCoV) and Betacoronavirus (BetaCoV) using partial Spike (S) gene sequences. Two samples (4.88%) tested positive for AlphaCoV, showing 97.08–99.27% sequence similarity, while one sample (2.44%) was positive for BetaCoV with 98.91% similarity. Due to the greater relevance of BetaCoVs to human health, the BetaCoV-positive sample underwent host identification via partial cytochrome oxidase I (COI) gene analysis and next-generation sequencing. The results revealed Rhinolophus coelophyllus as the likely natural reservoir. This study provides the first evidence of bat-derived BetaCoV genome in a commercial fertilizer in Thailand and highlights the importance of monitoring wildlife-derived products for emerging zoonotic viruses.